2020
DOI: 10.1002/clc.23458
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity as protective factors against mortality in nonischemic cardiomyopathy patients with an implantable cardioverter defibrillator

Abstract: Background: Previous studies have reported inconsistent results on the relationship between body mass index (BMI) and clinical outcomes in implantable cardioverter defibrillator (ICD) patients. Additionally, research on ICD patients with nonischemic cardiomyopathy (NICM) is lacking. Hypothesis: This study aimed to investigate the impact of BMI on mortality and ventricular arrhythmias (VAs) in NICM patients with an ICD. Methods: This study retrospectively analyzed the data from the Study of Home Monitoring Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Braun et al [ 50 ] found that in 763 patients, the 64 obese patients (BMI > 30 kg/m 2 ) had a significantly lower 6-year all-cause mortality compared with normal-weight patients (BMI 18.5-25 kg/m 2 ). Other studies also report similar results[ 22 - 24 ], supporting the present study. Nevertheless, some points still remain to be clarified.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Braun et al [ 50 ] found that in 763 patients, the 64 obese patients (BMI > 30 kg/m 2 ) had a significantly lower 6-year all-cause mortality compared with normal-weight patients (BMI 18.5-25 kg/m 2 ). Other studies also report similar results[ 22 - 24 ], supporting the present study. Nevertheless, some points still remain to be clarified.…”
Section: Discussionsupporting
confidence: 93%
“…In a cohort study of 110000 Japanese adults, BMI (≥ 25 kg/m 2 ) had a protective effect on pneumonia mortality [odds ratio (OR) = 0.7, 95% confidence interval (CI): 0.5-0.8][ 21 ]. Thus, in some diseases, obesity has emerged as a protective factor that could improve prognosis and reduce mortality[ 22 - 24 ]. Nevertheless, conflicting results are found in the literature[ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Easier studies conducted in this feld focused on obese patients with ICD, and the results showed an "obesity paradox" [19,20]. In the study by Echoufo-Tcheugui et al found that compared to normal-weight individuals, ≥65 years old patients with CRT-D who were underweight (BMI: 25-29.9 kg/m 2 ) had greater risks of mortality and hospitalization, while those who were overweight (BMI ≥ 30 kg/m 2 ) or obese had a lower mortality risk [19].…”
Section: Discussionmentioning
confidence: 97%
“…The effectiveness of secondary ICD prophylaxis has been confirmed by many studies and thus this prophylaxis is generally accepted [ 4 , 6 , 7 ]. On the other hand, the results of studies examining the effect of BMI are inconsistent [ 61 , 62 , 63 , 64 , 65 , 66 ]. Despite the well-known harmful effect on CV health, some studies showed a paradoxically favourable prognosis in overweight and obese cardiac patients.…”
Section: Discussionmentioning
confidence: 99%